Widespread and accelerating glacier retreat on the Lyngen Peninsula, northern Norway, since their 'Little Ice Age' maximum - Stokes, Chris R.; Andreassen, Liss Marie; Champion, Matthew R; Corner, Geoffrey D. (Journal of Glaciology, 2018)
Source at https://doi.org/10.1017/jog.2018.3 . The recession of mountain glaciers worldwide is increasing global sea level and, in many regions, human activities will have to adapt to changes in surface hydrology. Thus, it is important to provide up-to-date analyses of glacier change and the factors modulating their response to climate warming. Here we report changes in the extent of >120 glaciers on the Lyngen Peninsula, northern Norway, where glacier runoff is utilised for hydropower and where glacial lake outburst floods have occurred. Glaciers covered at least 114 km2 in 1953 and we compare this inventory with those from 1988, 2001 and a new one from 2014, and previously-dated Little Ice Age (LIA) limits. Results show a steady reduction in area (~0.3% a−1) between their LIA maximum (~1915) and 1988, consistent with increasing summer air temperatures, but recession paused between 1988 and 2001, coinciding with increased winter precipitation. Air temperatures increased 0.5°C per decade from the 1990s and the rate of recession accelerated to ~1% a−1 between 2001 and 2014 when glacier area totalled ~95.7 km2. Small glaciers (<0.05 km2) with low maximum elevations (<1400 m) experienced the largest percentage losses and, if warming continues, several glaciers may disappear within the next two decades.